Overcoming non‐idealities in electric vehicle charging management - Rauma, Kalle; Simolin, Toni; Rautiainen, Antti; Järventausta, Pertti; Rehtanz, Christian (IET electrical systems in transportation, 2021)
The inconvenient nature of non‐ideal charging characteristics is demonstrated from a power system point of view. A new adaptive charging algorithm that accounts for non‐ideal charging characteristics is introduced. The proposed algorithm increases the local network capacity utilization rate and reduces charging times. The first unique element of the charging algorithm is exploitation of the measured charging currents instead of ideal or predefined values. The second novelty is the introduction of a short‐term memory called expected charging currents. This makes the algorithm capable of adapting to the unique charging characteristics of each vehicle individually without the necessity to obtain any information from the vehicle or the user. The proposed algorithm caters to various non‐idealities, such as phase unbalances or the offset between the current set point and the real charging current but is still relatively simple and computationally light. The algorithm is compatible with charging standard IEC 61851 and is validated under different test cases with commercial electric vehicles.